Thursday

November 27, 2014

November 27, 2014

Posted by **Sira** on Monday, May 7, 2012 at 3:28am.

- Algebra 2 -
**Bosnian**, Monday, May 7, 2012 at 4:54amthird root ( 3 x ) + 5 + 4 = 0

third root ( 3 x ) + 9 = 0

third root ( 3 x ) = - 9

93 x = - 9 ^ 3

3 x = - 729 Divide both sides by 3

x = - 729 / 3

x = - 243

- Algebra 2 -
**Bosnian**, Monday, May 7, 2012 at 5:05amIf your expression mean :

third root ( 3 x + 5 ) + 4 = 0

then

third root ( 3 x + 5 ) = - 4

3 x + 5 = - 4 ^ 3

3 x + 5 = - 64

3 x = - 64 - 5

3 x = - 69 Divide both sides by 3

x = - 69 / 3

x = - 23

**Answer this Question**

**Related Questions**

Math I really need help! - Multiply and simplify by factoring. Assumem that all ...

algebra 2nd try - I need to simplify this 2/∛49 . I figured it out to be (...

Math Reiny? - Multiply and simplify by factoring. Assume that all expressions ...

algebra - I am really stuck, can someone please help me with this? Multiply and ...

math - ∛(270x )-∛(10x^4) subtract by simplifying by collecting like...

Simplify - Simplify the following number. ∛729 I think it is ∛9, but...

Math - ∛(y^13) ∛(16y^14)Multiply and simplify assume all expressions...

Math - Multiply and simplify by factoring. Assume that all expressions under ...

Please help! MATH - Multiply and simplify by factoring. Assume that all ...

Math anxiety!!! - Multiply and simplify by factoring. Assume that all ...